Association between EMIC wave occurrence and enhanced convection periods during ion injections - Remya, B.; Sibeck, D. G.; Ruohoniemi, J. M.; Kunduri, B.; Halford, G.; Reeves, G. D.; Reddy, R. V. (My University, 2020)
Electromagnetic ion cyclotron (EMIC) waves tend to occur during geomagnetic storms and solar wind pressure pulses. However, they have also been regularly observed even in the absence of these two drivers. These non-storm time and non-pressure pulse EMIC events are very well associated with individual nightside injections (Remya et al., 2018, https://doi.org/10.1029/2018JA025354). Nevertheless, not all substorm injections elicit wave activity. We examine the EMIC events excited during two substorm injections on 4 September 2015 and 1 October 2015. We find that injections that are associated with EMIC waves are also associated with enhanced ionospheric convection. The convective signatures occur at local times similar to those of the observed wave activity. Plain Language Summary Geomagnetic storms and magnetospheric compressions owing to solar wind pressure pulses are considered to be the two major drivers for electromagnetic ion cyclotron (EMIC) waves in the Earth's magnetosphere. However, it is found that substorms act as a major free energy source for these waves in the absence of geomagnetic storms or solar wind pressure pulses. In this study, we identify such non-storm time non-pressure pulse-driven EMIC waves and find that they are very well associated with substorm injections. We find direct evidence of correspondence of these injection-driven waves with enhanced ionospheric convection, which are manifestation of enhanced magnetospheric electric fields.
Keywords: Geomagnetic storms; Ion; Electromagnetic ion cyclotron waves; EMIC wave